MODETA JIHLAVA - Voralová, Monika (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Práce se zabývá revitalizací areálu bývalé textilní továrny Modeta v Jihlavě. Řeší její začlenění do struktury areálu přilehlé zoologické zahrady. Cílem práce je vytvořit multifunkční objekt, který poskytne nové prostory pro aktivity zoo. V objektu se nachází expozice nosorožců indických, drobných savců a plazů. Současně je v objektu navržena restaurace s kapacitou až 150 osob s možností ubytování. Stejně jako kongresový sál jsou tyto prostory přístupné ze vstupního foyer. Nad sálem se nachází IQ park a coworkingové prostory.

The work focuses on the revitalization of the former Modeta textile factory complex in Jihlava. It addresses its integration into the structure of the adjacent zoo area. The aim of the project is to create a multifunctional facility that will provide new spaces for zoo activities. The building houses exhibitions of Indian rhinoceroses, small mammals, and reptiles. Additionally, the building includes a restaurant with a capacity of up to 150 people and accommodation options. Like the congress hall, these spaces are accessible from the entrance foyer. Above the hall, there is an IQ park and coworking spaces. New changing rooms for zoo employees are designed in connection with the technical yard.
MODETA JIHLAVA
Keywords: Modeta; Jihlava; multifunkční objekt; revitalizace; transformace; brownfield; zoo.; Modeta; Jihlava; multifunctional object; revitalization; transformation; brownfield; zoo.